Effectiveness of management of higher public education from the Baldrige excellence program - Morais, Greiciele Macedo; Martins, Henrique Cordeiro; Ziviani, Fabricio (Revista de Administração da UFSM, 2020)
Purpose – The objective of this article is to analyze the effectiveness of higher education management, according to the Baldrige Excellence Model in a Public Institution of Higher Education in Minas Gerais, based on the perception of public workers. Design/methodology/approach – A quantitative survey was carried out with the application of questionnaires to university employees. The collected data were submitted to multivariate statistical analysis using the Partial Least Squares - Structural Equation Modeling (PLS-MEE) and Covariance (MEE-CB). Findings – The methods adopted confirmed that Leadership, Strategic Planning, Focus on the Client, Measurement of Knowledge, Analysis and Management, Focus on the Workforce and Focus on the Operation explain more than 75% of the effectiveness of the management of an IPES. This research corroborates with the Baldrige Education Criteria for Performance Excellence (2019), even if applied in Brazil, a different context from the original model. Research limitations/implications – The customer's perception was not collected in this research. For a greater depth of analysis of the construct and model, it appears that it is relevant to include the participation of the client in future research and expand the units of analysis. Originality/value – Know the elements that affect the management effectiveness of public institutions of higher education. With the model, the effectiveness of management is significantly explained, but the simultaneous correlation between all constructs is not proven and there is little leadership contribution. These results demonstrate the need for advances in the specifics of the model for the management of this type of institution.